Work Loyalty, Communication, and Supervision Their Influenc on Work Ethic and Performance of Police Members in the Criminal Investigation Unit of the Bone Bolango Police Resort - Ibrahim, Meimoon; Yakup, Yakup; Karundeng, Deby Rita; Abdillah, Mohamad Rizal (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
The aim of this study is to analyze the influence of job loyalty, communication, and supervision on the work spirit and performance of members of the Criminal Investigation Unit (Satuan Reserse dan Kriminal) of Bone Bolango District Police. The population of the study consisted of 127 respondents selected using a census method. The analytical technique used to address the research problem and test hypotheses was Path Analysis, aided by Statistical Product Service Solution (SPSS) and Lisrel software for data analysis. The findings of this research are as follows: (1) job loyalty has a positive and significant direct effect on work spirit, (2) communication has a positive and significant direct effect on work spirit, (3) supervision has a positive and significant direct effect on work spirit, (4) job loyalty has a positive and significant direct effect on performance, (5) communication has a positive and significant direct effect on performance, (6) supervision has a positive and significant direct effect on performance, (7) work spirit has a positive and significant direct effect on performance, (8) job loyalty has a positive and significant indirect effect on performance through work spirit, (9) communication has a positive and significant indirect effect on performance through work spirit, (10) supervision has a positive and significant indirect effect on performance through work spirit.